Understanding Public Sector Employees' Ethical Engagement in the Digital Era: Evidence from China - Xiangyu Bian (European Journal of Management Issues)
Purpose: This research investigates how Chinese public sector employees perceive and approach administrative ethics in the digital age. The study aims to understand how attitudes, organizational culture, and perceived organizational support influence satisfaction with ethical practices, emphasizing the mediating role of behavioral intention.